REDESIGN MODEL BISNIS DENGAN PENDEKATAN BLUE OCEAN STRATEGY : STUDI KASUS E-BUSINESS SOBAT BANGUN - Zailani, M. Ardy; Nasution, Arman Hakim (LPPM STIE Muhammadiah Bandung, 2025)
Sobat Bangun is an innovative platform to help the process of building houses efficiently. Sobat Bangun's business performance has not only experienced an increase in revenue generated, but a decrease in platform project transactions. The research objective is to evaluate and determine the right business model needed so that Sobat Bangun's business can produce good performance. The results of the Redesign Business Model on the Customer Segments element are creating B2B and B2B2C customer segments such as state-owned companies and housing developers by utilizing internal strengths. Value Proposition, by improving the value platform for more optimal utilization and customer experience and clustering partner choices. Channel, creating communication channels through inter-institutional cooperation initiated from the company's top management approach. Customer relationship, development of current platform technology in the form of a web platform / mobile application for customers who have made agreements to monitor and communicate regarding project progress and other services. Revenue stream, shifting the focus to projects with greater value and higher margins (Project Mid To High) and optimizing paid visitation services and construction management services. Key Activities, increased market penetration focusing on B2B customer service. Key Resources, increase personnel competency through internal development and acquisition of external talent.